Análise comparativa de redes interfirmas de instituições de ensino superior - Zaneti, Gislaine Barbosa; Fusco, José Paulo Alves [UNESP]; Rocha, Regina Ferreira da (My University, 2013)
Organizations have been facing several challenges to survive in a world in constant transformation. In light of that, new management models need to be incorporated to the organizational dynamics in order to achieve competitive advantages. The inter-firm networks establish a particular form means of cooperation as a fundamental element, as there can be ties of diverse nature to justify the relationships. These are interorganizations or inter-firms, formed by people who maintain the relationships to improve the overall performance of the network and of the participants. Thus, the Education Institutions, considered as organizations, which have the objective to disseminate knowledge and form professionals who contribute to the growth of a nation, also make use of this type of arrangement. Considering the raised questions, this article aims to demonstrate the applicability of a business network mapping technique at Higher Education Institutions. It also presents the possibility to perform the comparative analysis of the intensity of the relationship observed in a private and in a public institution, in the State of São Paulo. By applying the comparative analysis, this study also presents the relationship among the people involved at strategic and tactical levels of each institution, taking into account each one s peculiarities.

Este artigo foi obtido ao longo das atividades do Grupo de Pesquisas NETPRO - Redes de Empresas e Cadeias de Fornecimentos, cadastrado pela UNESP junto ao CNPq.Foi selecionado entre os 10 melhores do VIII Encontro Mineiro de Engenharia de Produção - EMEPRO 2012
Comparative analysis of inter-firm networks in higher education institutions
Keywords: Networks; Inter-firm networks; Higher education institutions; Relationship intensity; Redes; Redes interfirmas; Instituição de ensino superior; Intensidade de relacionamentos